Sexual selection on male vocal fundamental frequency in humans and other anthropoids - Puts, David A. (Proc Biol Sci, 2016)
In many primates, including humans, the vocalizations of males and females differ dramatically, with male vocalizations and vocal anatomy often seeming to exaggerate apparent body size. These traits may be favoured by sexual selection because low-frequency male vocalizations intimidate rivals and/or attract females, but this hypothesis has not been systematically tested across primates, nor is it clear why competitors and potential mates should attend to vocalization frequencies. Here we show across anthropoids that sexual dimorphism in fundamental frequency (F(0)) increased during evolutionary transitions towards polygyny, and decreased during transitions towards monogamy. Surprisingly, humans exhibit greater F(0) sexual dimorphism than any other ape. We also show that low-F(0) vocalizations predict perceptions of men's dominance and attractiveness, and predict hormone profiles (low cortisol and high testosterone) related to immune function. These results suggest that low male F(0) signals condition to competitors and mates, and evolved in male anthropoids in response to the intensity of mating competition.